Early Transcranial Color-Coded Sonography as a predictor of Hemorrhagic Transformation after Thrombectomy - Costa, André Jorge Assunção (2018)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina